Effects of Non-Monetary Reward systems on Employee Performance in Universities in Kenya: A Case of Selected Universities - Aduda, Roseline Atieno (JOOUST, 2018)
The complexity of today's business environment has imposed continually changing settings in which organizations or institutions compete for survival. As a result, special emphasis is placed on acquiring and retaining quality employees as this is seen as a key factor underpinning organizational success. The rewarding mechanisms are also changing which not only means things with tangible values but also those that may satisfy other needs of staff including work life balance, which may just be creating a supportive environment, that is purely non-monetary in nature. These non-monetary rewards are acting more as drivers to both retention and motivators that have led most valued staff to leave and establish their own establishment that would provide room for satisfaction of their endeavors. The purpose of the study was to determine the effects of non-monetary reward systems on employee performance in universities. Specifically, the study sought to establish the effects of training, promotional opportunities, autonomy of employee, and recognition and appreciation on employee performance in universities: A case of selected universities. The study employed correlation research design and the target population was 870 employees of the selected universities and the sample size was 274. The researcher used stratified and random sampling method to select respondents. The study was anchored on Theoretical and Empirical review. The motivational theories used in this study included Maslow's Hierarchy of needs theory, McClelland's Theory of needs, Vroom's Expectancy theory, Adam' Equity Theory, Skimmer's Reinforcement theory, Alderfer's ERG Theory and Herzberg Two Factor theory. Quantitative data was collected by use of questionnaire and administered to the respondents by the researcher and two research assistants. Interview schedule was also used for collecting qualitative data. Data analysis was both descriptive and inferential statistics i.e. by use of mean, frequency, standard deviation and correlation and regression analysis. Findings were presented using tables. Qualitative data from interviews was analyzed using thematic analysis as per the objectives of the study. The study found out that training and development, promotional opportunities, employee autonomy and recognition and appreciation affect employee performance. The study concluded that non-monetary reward systems such as training, promotion opportunities, employee autonomy and recognition and appreciation play important role in the employee performance. Therefore, the study recommended that the universities management should embrace non-monetary reward systems because it will help in boosting their morale and improving employee performance.